(547) Marginal Productivity Wage Theory and Subsistence Wage Theory in Egyptian Agriculture نظرية الإنتاجية الحدية للأجور ونظرية الأجر الأساسي في الزراعة المصرية - Hansen, Bent (The Institute of National Planning, 2025)
This study addresses agricultural wages within the framework of modern growth theory, analyzing agricultural wages through two main hypotheses of wage determination. The results derived from time series analysis examine real wages and labor's share in agriculture from 1914 to 1961. It also discusses wage differentials among Egyptian villages and the impact of statutory minimum wages. In conclusion, final remarks summarize the findings and practical significance of the study. The statistical appendix includes several indicators, such as the index of the value of marginal productivity of labor, the wage index, and the cost-of-living index, reflecting changes in real wages and labor share in the agricultural sector.